Methodology of open economic science in a foreign language: theory and practice - Шмаровоз, Олена Василівна; Павлова, Олена Миколаївна; Ляшенко, Оксана Миколаївна; Матійчук, Любомир Павлович (Національний технічний університет «Харківський політехнічний інститут», 2024)
Abstract. In today’s world, where scientific research plays a crucial role in addressing global challenges, openness and accessibility of scientific knowledge have become fundamental principles for the successful development of society. The concept of open science, which promotes the free exchange of scientific information and access to research results, data, and methodologies, creates new opportunities for collaboration, innovation, and improving the quality of scientific work. For Ukraine, which aims to strengthen its scientific potential and integrate into the global scientific community, developing open science is an important step toward enhancing its competitiveness on the world stage. By embracing open science, Ukraine can tap into a wealth of international knowledge, foster collaboration, and accelerate its scientific progress. The purpose of the article is to provide a thorough study of the theoretical and practical aspects of researching the methodological foundations of open economic science in a foreign language. Materials and Methods. The methodology of open science has become one of the leading directions in modern scientific research, focused on increasing the accessibility, transparency, and effectiveness of scientific activities. Open science involves the free exchange of knowledge, publication of research results in open access, and close collaboration between scientists from different countries. These principles are particularly relevant for international research, where language barriers, such as the need for translation and interpretation, and cultural differences, which can affect the interpretation and application of research findings, can hinder effective interaction and knowledge exchange. However, international collaboration is also a key strength of open science, as it allows researchers to leverage each other's expertise and resources, and to address global challenges more effectively. Prospects. The article highlights the importance and specific features of the development of open science in Ukraine, particularly regarding access to international scientific research. The main issues, such as limited funding, language barriers, and underdeveloped infrastructure of open repositories, are analyzed. It is demonstrated that the implementation of open science principles will contribute to improving the quality of research, fostering international cooperation, and boosting innovation in Ukraine. The importance of access to foreign research for adapting to global scientific and technological trends is particularly emphasized. The article proposes possible paths for the development of open science in Ukraine, including the improvement of legislation, development of infrastructure, and support for international scientific initiatives such as joint research projects, exchange programs, and collaborative publications. Policymakers play a crucial role in these efforts, as they can enact legislation that promotes open science and allocate resources to support it. The adoption of open science principles will allow Ukraine to join global scientific processes, enhance the accessibility of scientific knowledge, bridge the gap between science and society, and stimulate innovative development. The article addresses the key aspects of the importance of open science for the Ukrainian scientific community and national development, especially in the context of international cooperation, economic opportunities, and improving the quality of education.
Keywords: open access; open science; scientific research; foreign research; repository